Business Skills For Your Career In Retail - Ashley, Vic; Ashley, Sheila; Morris, Gill (Business consultant); City and Guilds of London Institute (London : City & Guilds, 2012)
This book gives aspiring entrepreneurs the practical advice and skills they need to set up and manage a retail business. Key business skills are put into a vocational context with practical advice and activities, giving readers the tools to make a success of their businesses.
Formerly CIP.
Includes bibliographical references and index.
Keywords: Retail trade -- Great Britain